Requirements for De Novo Initiation of RNA Synthesis by Recombinant Flaviviral RNA-Dependent RNA Polymerases - Ranjith-Kumar, C. T. (American Society for Microbiology, 2002)
RNA-dependent RNA polymerases (RdRps) that initiate RNA synthesis by a de novo mechanism should specifically recognize the template initiation nucleotide, T1, and the substrate initiation nucleotide, the NTPi. The RdRps from hepatitis C virus (HCV), bovine viral diarrhea virus (BVDV), and GB virus-B all can initiate RNA synthesis by a de novo mechanism. We used RNAs and GTP analogs, respectively, to examine the use of the T1 nucleotide and the initiation nucleotide (NTPi) during de novo initiation of RNA synthesis. The effects of the metal ions Mg(2+) and Mn(2+) on initiation were also analyzed. All three viral RdRps require correct base pairing between the T1 and NTPi for efficient RNA synthesis. However, each RdRp had some distinct tolerances for modifications in the T1 and NTPi. For example, the HCV RdRp preferred an NTPi lacking one or more phosphates regardless of whether Mn(2+) was present or absent, while the BVDV RdRp efficiently used GDP and GMP for initiation of RNA synthesis only in the presence of Mn(2+). These and other results indicate that although the three RdRps share a common mechanism of de novo initiation, each has distinct preferences.